DESIGN EVALUATION OF FLYWHEEL USED IN DIESEL ENGINE CAR FOR VARIABLE TORQUE LOAD - Mallikarjuna, K.; Srikanth, D. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
A flywheel is a rotating mechanical device that is used to store rotational energy. Flywheels have a significant moment of inertia and thus resist changes in rotational speed. The amount of energy stored in a flywheel is proportional to the square of its rotational speed. Energy is transferred to a flywheel by applying torque to it, thereby increasing its rotational speed, and hence its stored energy. Conversely, a flywheel releases stored energy by applying torque to a mechanical load, thereby decreasing its rotational speed.Countering the requirement of smoothing out the large oscillations in velocity during the cycle of a mechanism system, a flywheel is designed and analyzed. Firstly, based on the dynamic function specifications of the system, the main features of the flywheel have been initially determined in a traditional way. Then, the finite element dynamic analysis of a flywheel have been carried out to get superior performances.The geometrical modeling is to done in Pro/E and Analysis is to done by using Ansys